2022
DOI: 10.3390/biomedicines10123170
|View full text |Cite
|
Sign up to set email alerts
|

Detection of BRCA1, and BRCA2 Alterations in Matched Tumor Tissue and Circulating Cell-Free DNA in Patients with Prostate Cancer in a Real-World Setting

Abstract: Background: Poly (ADP-ribose) polymerase (PARP) inhibitors are approved for patients with metastatic castration-resistant prostate cancer harboring deleterious or suspected deleterious BRCA1 and/or 2 mutations. Identifying patients with prostate cancer harboring these mutations may be challenging. Circulating cell-free DNA (cfDNA) provides an avenue for an easier detection of these mutations. Herein, we aimed to evaluate the concordance of BRCA mutations in the tumor tissue and cfDNA in patients with metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…In the present study, it has been demonstrated that analysis of archival samples in mCRPC samples is feasible using this NGS panel, and the percentage of mutations observed in BRCA1/BRCA2 and HRR genes is overlaps with that reported in the literature [8,9,38]. Another possible alternative in case of unavailable metastatic material could be to perform the test on liquid biopsy (e.g., plasma or urine [39,40]), although the application of this method is challenging due to the lack of standardized analysis methods, the need for high analytical sensitivity, and expertise in data analysis [39].…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, it has been demonstrated that analysis of archival samples in mCRPC samples is feasible using this NGS panel, and the percentage of mutations observed in BRCA1/BRCA2 and HRR genes is overlaps with that reported in the literature [8,9,38]. Another possible alternative in case of unavailable metastatic material could be to perform the test on liquid biopsy (e.g., plasma or urine [39,40]), although the application of this method is challenging due to the lack of standardized analysis methods, the need for high analytical sensitivity, and expertise in data analysis [39].…”
Section: Discussionmentioning
confidence: 60%